A FRAMEWORK FOR CONVERTING SQL QUERIES FROM NATURAL LANGUAGE - K.N, Balapradeep; U J, Ujwal; C K, Savitha; M R, Prajna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The database interface, called the "natural language interface", uses natural language to allow users to access data without the need for SQL queries. Using query language to interact with databases is always a sophisticated issue. Due to this complexity, the client must use the clear reports that are included in some pre-executed programming projects when using information that is already present in database points of confinement. But, users can make it possible for each nonprofessional user to ask questions and provide requirements in natural language, which the computer can then process to produce the appropriate data. This study introduces a system developed using the "Natural Language Interface to Database" (NLIDB). This approach has led to the emergence of "experts" who can detect compound sentences in English and use them in lessons. After parsing the input sentences, the natural language is converted to SQL.